Identification of Species in the Aromatic Spice Family Apiaceae Using DNA Mini-barcodes - Parveen, Iffat; Techen, Natascha; Khan, Ikhlas A. (Planta Medica, 2019)
The species of the aromatic plant family Apiaceae are mainly used as spices and foods, but the family also includes medicinal and some poisonous plant species. Due to the similar chemical compounds or aroma and morphology, the poisonous species are often mistaken for the edible aromatic species. It is therefore imperative to correctly identify the species present at the initial raw stage samples to ensure product safety and efficacy. At the molecular level, plant species can be identified using DNA loci either from nuclear or plastid genome with easily available universal oligonucleotides, a technique called DNA barcoding. However, this is possible when single-species plant material is present but may not work on a mixture of plants species. Another disadvantage is that using universal oligonucleotides is of limited help, especially if the adulterating material is present in low quantities. On the other hand, if using the species-specific oligonucleotides, only single specific adulterating plant material could be detected and, consequently, the unexpected adulterants may go undetected. Therefore, in the current work, four degenerated oligonucleotides from ITS1 and ITS2 regions of the nuclear genome were designed that can bind to a variety of Apiaceae genera only and not to other genera belonging to different plant families. These family-specific oligonucleotides were able to amplify a diagnostic PCR product from 16 Apiaceae species that, upon sequencing, revealed the identity of the plant it was derived from. The size of these products is around 140 bp for ITS1 and approximately 80 bp for the ITS2 region. The size range of the amplified products falls in the category of a desired mini-barcode size to be used for damaged/fragmented DNA and next generation sequencing.
Keywords: Adulteration; Apiaceae; aromatic species; DNA mini-barcodes; family-specific oligonucleotides; universal oligonucleotides